Conglutinatio cervicis uteri orifici externi: a rare disorder of uterine cervix - Hatirnaz, Safak (The European Research Journal, 2015)
Cervical conglutination is quite rare complication of labor that can be misinterpreted as fully dilated totally effaced intact amniotic membrane, and in inexperienced hands trying to open the membrane results in the catastrophic outcome. Only a few articles present in literature and most of them are very old articles. Sharing this rare disorder as an experience may increase the attention of obstetricians and midwives to be careful about such condition in prolonged labor cases.